Linguistic strategies of politeness in Malaysian chatrooms / Nur Najla Zainal Anuar - Nur Najla, Zainal Anuar (2012)
This study delves into the issues of language and politeness among chatters who use the chat room to communicate via the internet. The medium of communication used in this study is the Yahoo instant messenger where it is a private web based chat room, created specifically for this purpose. In order to find out if politeness is used by chatters in this „faceless‟ community, it is investigated in terms of language forms and functions through the use of emphatic stress, capitalization and excessive punctuation marks, greetings, leave-taking, profanity language as well as a self censorship. Later on, language use is then explored in terms of linguistic expressions of politeness using the Brown and Levinson‟s Politeness Theory. The participants of this study are divided into two groups of ages and genders. The first group includes male (10) and female (10) chatters of the range 15-20 of age. Another group includes male (10) and female (10) chatter of the range 21-26 of age. These groups are the representatives of the Malaysian chatters population. The methods employed for this study is the mixed approach in which the qualitative approach is used to describe the use of language in the chat room in order to relate it to the issue of politeness. On the other hand, the quantitative approach is used in order to study the relation of age and gender in terms of the use of politeness in the chat room. Overall, the results indicate that different age groups employ different linguistic strategies and politeness theories to appear polite or impolite. Gender similarities were noted too especially in terms of language use. This report typically reflects the level of politeness found amongst the Malaysian chatters of different age groups and gender. Finally, the findings of the study serve to provide a variety of insights into the ways chatters present themselves and interact with others in chat room.